Bead stringing - Schulz, Carolyn (Jewelry school, 2018)
Beaded jewelry is popular among crafters as it requires very little by way of tools or materials. Jewelry School: Bead Stringing, written by Carolyn Schulz, author of Jewelry School: Let's Start Beading, helps the reader to make attractive, wearable items of beaded jewelry in no time. Bead Stringing is a progression from Let's Start Beading, and focuses on the specifics of bead stringing, teaching the reader more advanced beading techniques.The book is divided into three sections: beading on tiger tail, beading on thread, and decoration and pattern. Through clear, colorful step-by-step photographs Carolyn Schulz guides the reader through the whole process and focuses on a series of projects that readers will be impatient to try for themselves.